DEVELOPMENT OF AI-BASED E-MODULES ON CELL MATERIALS TO IMPROVE STUDENT LEARNING OUTCOMES AND CREATIVITY - Ahmad Musholli Qurba Maulana; Wiyanto wiyanto; Arif Widiyatmoko (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2026)
Learning of cell material in science education often faces several challenges, particularly low student learning outcomes and limited student creativity due to the lack of interactive and innovative learning media. In addition, the integration of artificial intelligence (AI) in learning resources is still rarely implemented in classroom practice. Therefore, the development of innovative digital teaching materials is needed to support more effective and engaging learning. This study aims to develop an AI-based e-module on cell learning in science education to improve learning outcomes while fostering student creativity. This study employed a Research and Development (R&D) method using the 4-D model (Define, Design, Develop, and Disseminate). The effectiveness of the developed e-module was tested using a true experimental design with a pretest–posttest control group. Subjects included media experts, learning material experts, and students at MTs Mada Nusantara. The results showed that the AI-based e-module on cell learning achieved a high level of validity and was declared highly feasible by both media experts and learning material experts. Learning outcomes were improved in the experimental class, with the average score increasing from 68.96 to 76.58. Students’ creativity also improved, with most students categorized as creative to very creative after using the module. The average practicality score from teachers and students was 3.66, indicating that the e-module is easy to use, effective, and relevant as a teaching material to support the learning process. This study contributes to the development of innovative AI-based digital learning media in science education and implies that AI-based e-modules can be effectively used as interactive teaching materials to enhance students’ conceptual understanding, creativity, and technology-integrated science learning.